RESPONSE OF FBG-BONDED GRAPHENE PLATE AT DIFFERENT APPLIED STRESS LOCATION (Jurnal Teknologi (Sciences & Engineering), 2016)
In this study, the response of a FBG-bonded-graphene plate at different applied stress location is demonstrated. The sensing element utilized for this purpose is a 35.9-mm FBG sensor bonded onto the surface of a graphene plate. The lateral displacement is changed with corresponding increase or decrease in the FBGâ€™s curvature. The change in center wavelength of the reflected spectrum is almost linear, without a significant hysteresis effect. It was also observed that the sensitivity of the FBG changes for location of applied stress.Â  Likewise, the area under the reflection curve is observed to increase with increase in strain level, indicating an increase total power reflected. This is verified by an increase in the voltage output as observed from the oscilloscope.Â